Theoretical Knowledge in the Mohist Canon - Schemmel, Matthias. author. aut Link
X, 207 p. 1 illus.
Keywords: This open access book presents a new translation, interpretation and analysis of selected passages from the so-called Mohist Canon, a Chinese text from ca. 300 BCE, and discusses the role of the text in the world history of science, arguing that it represents an early emergence of theoretical, systematized knowledge that is independent from parallel developments in ancient Greece. It is aimed at historians of science, of knowledge and of philosophy, and generally at readers interested in these topics from an intercultural perspective and particularly with respect to China.